Change in tourist trends as a result of restrictions caused by the COVID-19 pandemic - Saenko, Natalya; Shubtsova, Lyudmila; Khmelev, Igor; Otcheskiy, Ivan; Sakhno, Aleksandr; Sinyukov, ﻿Vasily (Anais Brasileiros de Estudos Turísticos, 2022)
As the novel coronavirus infection (COVID-19) continues to spread throughout the world, the tourism industry operates under numerous social distancing constraints, which has a negative impact on demand, the economic performance of tourism businesses, and also leads to staff layoffs and numerous bankruptcies in the industry. The purpose of the article is to investigate changes in the established global trends in tourism under the influence of restrictions caused by the COVID-19 pandemic. The study presents an analysis of the impact of the COVID-19 pandemic on the tourism industry. The macrotrends in tourism before the introduction of restrictions due to the COVID-19 pandemic and the trends that emerged in tourism in the course of the pandemic are identified. The study suggests that the trends that made their appearance in tourism during the pandemic can contribute to the industry’s recovery from the crisis in the post-pandemic period. At the same time, the prospects for the tourism sector remain extremely unclear. The changes brought about by the pandemic force the authorities of virtually all countries of the world, especially those in which tourism is quite a significant sphere of development, to take a different approach to the formation of strategies and programs for the development of the tourism industry.